Post a New Question


posted by .

Find (a) f X g , (b) g X f, and (c) f X f

f(x) = 3sqrt x-1 g(x) = x^3 + 1

For the f(x) the 3 is little above the sqrt sign.

my answers were:

(a) = 3sqrt x^4 -1

(b) = x^4 -1

(c) = 6sqrt x+1

These answers are wrong but I do not know how to do this

  • Pre-Cal -

    f(x)= cubrt(x-1)

    f(g(x))= cubrt(x^3+1-1)=x
    g(f(x)= f(x)^3+1=(cubrt(x-1)^3-1=x
    f(f)= cubr(cubrt(x-1)-1) which might be simplified, but I don't see it now.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question